Regionalisation of globalised innovation : locations for advanced industrial development and disparities in participation - Hilpert, Ulrich, 1951- (Routledge studies in the modern world economy, 2003)
This book examines local 'Islands of Innovation' where research and industrial expertise are concentrated, along with areas where traditional industrial regions have passed through a process of innovative restructuring.